The 1746 earthquake and the gestation of the Lima conspiracy of 1750 - O’Phelan Godoy, Scarlett (2022)
This article seeks to establish connections between the natural disaster of 1746 and the Lima conspiracy of 1750, as part of the mid-eighteenth century context, when social movements of a certain magnitude underwent a process of maturation. The distress that the earthquake caused in the poor population, as a result of hygienic deficiencies, led to outbreaks of social unrest. From the riots of the Indian potters in the Santa Ana neighborhood in 1747, to the plan forged three years later by Indians and other social actors involved in the conspiracy, collective fear was used as a control mechanism and an opportunity for insurrection.